The role of forest resources in income inequality in Cameroon - Makoudjou, A.; Levang, P.; Tieguhong, J.C. (Informa UK Limited, 2017)
The present study focuses on forest incomes of households around forest concessions in Cameroon. The contributions of forest income to the economy and well-being of households were measured and the explanatory factors for heterogeneity determined. We used the Gini index to evaluate the distribution of household forest incomes and their influence on well-being and income inequality amongst forest-dependent households. Three TOBIT econometric models with sample selection were estimated to identify factors that influence the level of each source of forest income. Results from our analysis show that forest contributes on average 38% of total annual household income with 19, 13 and 6% from illegal logging, hunting and non-timber forest products (NTFPs) of vegetal origin, respectively. Forest income overall contributes in increasing disparities among people by 3%. Income from illegal logging was found to be a major source of income inequality while other forest income sources such as NTFPs and hunting slightly reduced income inequality. Access to villages and the amount of agricultural income were the main factors that explained the differences in forest income.